Overcoming drug-resistant herpes simplex virus (HSV) infection by a humanized antibody - Krawczyk, Adalbert; Arndt, Michaela; Große-Hovest, Ludger; Weichert, Wilko; Giebel, Bernd; Dittmer, Ulf; Hengel, Hartmut; Jäger, Dirk; Schneweis, Karl E.; Eis-Hübinger, Anna Maria; Roggendorf, Michael; Krauß, Jürgen (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Despite the availability of antiviral chemotherapy, herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infections remain a severe global health problem. Of particular concern is the growing incidence of drug resistance in immunocompromised patients, which stresses the urgency to develop new effective treatment alternatives. We have developed a humanized monoclonal antibody (mAb hu2c) that completely abrogates viral cell-to-cell spread, a key mechanism by which HSV-1/2 escapes humoral immune surveillance. Moreover, mAb hu2c neutralized HSV fully independent of complement and/or immune effector cell recruitment in a highly efficient manner. Prophylactic and therapeutic administration of mAb hu2c completely prevented infection-related mortality of severely immunodeficient mice being challenged with a lethal dose of HSV-1. The high neutralization capacity of mAb hu2c was fully maintained toward clinical HSV isolates being multiresistant to standard antiviral drugs, and infection was fully resolved in 7/8 nonobese diabetic/SCID mice being infected with a multidrug resistant HSV-1 patient isolate. Immunohistochemical studies revealed no significant cross-reactivity of the antibody toward human tissues. These features warrant further clinical development of mAb hu2c as an immunotherapeutic compound for the management of severe and particularly drug-resistant HSV infections.
Gesehen am 27.10.2021